Household-Scale Hydroponic Farming to Improve Food Security Among Fishing Communities in Lagaruda Village, Takalar Regency - asbar asbar; Abdullah Abdullah; Asmidar asmidar (Universitas Muhammadiyah Sidenreng Rappang, 2026)
Limited land availability and high dependence of coastal communities on the fisheries sector have led to low diversification of food sources and household income in Laguruda Village, Sanrobone District, Takalar Regency. This Community Partnership Program (PKM) aims to improve community knowledge and skills in hydroponic cultivation as an alternative for utilizing home yard spaces. The implementation method employed a participatory approach through socialization, hands-on training, and mentoring stages. The program was conducted over five months involving a community business group (KUBE) as the main partner. The results indicated a significant improvement in participants’ knowledge and technical skills in hydroponic practices, including seedling preparation, installation setup, and plant maintenance. Furthermore, hydroponic application optimized the use of limited land, supported household food security, and created opportunities for small-scale income-generating activities. High participant involvement contributed to the program's success; however, further assistance is needed to ensure long-term sustainability.